Landing from ship, boarding the canoe: Gioconda Mussolini, 1886-1938 - Ciacchi, Andrea (Revista de Antropologia, 2015)
The main objective of this paper is the reconstruction of a specific aspect of biographical and intellectual career of Gioconda Mussolini, who was, successively, undergraduate student, assistant and professor at the Faculty of Philosophy, Sciences and Letters (FFCL) of the University of São Paulo from 1935 to 1969: her school journey, from childhood to degree in FFCL. I propose, however, to go even further in time and space, in order to include in this trajectory the arrival of her father's family from Italy, in 1886, and her school experience in the city of São Paulo, in the twenties and thirties of last century. My hypothesis is that this course is largely determined by her belonging to a special portion of the “Italian-paulistan” experience in the early twentieth century, on the one hand, and on the other, that it determines her intelectual option to the Social Sciences and Anthropology